ANALISIS PERAN FINTECH SYARIAH DALAM PEMBIAYAAN UNBANKABLE PEOPLE - Dias Rizkiaisha (2023)
Financial Technology (Fintech) is one of the pillars for MSMEs to seek capital to increase MSME businesses. To improve the quality and quantity of MSMEs, fintech is here to help finance MSMEs who want to advance their business. The purpose of writing this Final Project is to discover Sharia fintech's role in funding unbankable people. To find out how fintech x deals with risks to financing MSMEs. To learn the development of unbankable people after receiving financing from Islamic fintech. The method used is descriptive qualitative, with primary and secondary data sources. Methods of data collection are done by observation and interviews. The writing results show that improving the quality and quantity of business is very important in increasing MSME income, especially for fish farmers. To improve the quality and quantity of fish, farmers need capital to improve their business to be more advanced and go global.